2010
DOI: 10.1097/spc.0b013e328340744d
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and symptoms of depression in advanced heart failure patients and their partners

Abstract: 2 Purpose of reviewTo provide an overview of factors related to quality of life and symptoms of depression in heart failure patients and their partners. Furthermore, to give an overview of interventions that can be effective in improving their quality of life and decrease depressive symptoms. Recent findingsQuality of life of patients with heart failure and their partners is poor compared to their age-matched peers from the general population and also compared to patients suffering from other chronic diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 57 publications
(54 reference statements)
3
48
0
4
Order By: Relevance
“…It is characterised by a debilitating late course, with increasingly frequent hospitalisations and considerable morbidity besides the obvious mortality [2]. Heart failure affects quality of life (QoL) more profoundly than many other chronic diseases [3]. Even though QoL is a major concern, it appears that clinical management as well as research efforts do not focus sufficiently on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterised by a debilitating late course, with increasingly frequent hospitalisations and considerable morbidity besides the obvious mortality [2]. Heart failure affects quality of life (QoL) more profoundly than many other chronic diseases [3]. Even though QoL is a major concern, it appears that clinical management as well as research efforts do not focus sufficiently on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…HRQoL pada pasien gagal jantung kongestif wanita dikarenakan secara fisik, mental wanita lebih lemah dibandingkan pasien gagal jantung kongestif laki-laki, serta wanita memiliki tingkat depresi yang lebih tinggi dibandingkan dengan laki-laki [17].…”
Section: Penelitian Lain Melaporkan Bahwa Rendahnyaunclassified
“…Patients with HF often report poor HRQoL (Juenger et al 2002, Falk et al 2013, often poorer than in other chronic conditions (Jaarsma et al 2010b). Patients with HF have also reported poorer HRQoL compared to an agematched group of elderly people , Lesman-Leegte et al 2009) and have consistently reported significantly lower in the area of physical health (Lesman-Leegte et al 2009).…”
Section: Impact On Everyday Life and Quality Of Lifementioning
confidence: 99%
“…Patients with HF have also reported poorer HRQoL compared to an agematched group of elderly people , Lesman-Leegte et al 2009) and have consistently reported significantly lower in the area of physical health (Lesman-Leegte et al 2009). Heart failure together with co-morbidity has an impact on HRQoL (Franzen-Årestedt et al 2007), where progressing disease severity and increasing levels of co-morbidity are associated with poorer quality of life in patients with HF (Jaarsma et al 2010b). Co-morbidities also influence the patient's self-care, where the presence of more than one illness has been shown to make it more complicated for the patients to manage their illness (Jeon et al 2010).…”
Section: Impact On Everyday Life and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation